2019
DOI: 10.1007/978-3-030-32169-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Cascading Effects in Interdependent Critical Infrastructures

Abstract: Critical Infrastructures (CIs) are resources that are essential for the performance of society, including its economy and its security. Large-scale disasters, whether natural or man-made, can have devastating primary (direct) effects on some CI and significant indirect effects (cascading effects) on other CIs, because CIs are interconnected and depend on each other's services. Recent work by Laugé et al. expressed the dependency values among CIs as dependency matrices for various durations of the primary CI fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, there is general agreement that CIs include government, telecommunication based on ICT (information and communication technology); financial sector; energy supply; water transportation systems; health sector; and security services (first responders, police, military)." (Abdelgawad et al, 2018;Abdelgawad and Gonzalez, 2019) Table 2 Critical infrastructure definitions "When we consider CIs, we have to take into account that they are not simply 'physical' plants and networks. In fact, they contain not only a physical layer, but are also made of 'cyber' components and systems, and include human organisations that manage and supervise the daily operations of the infrastructure."…”
Section: Tablementioning
confidence: 99%
See 4 more Smart Citations
“…However, there is general agreement that CIs include government, telecommunication based on ICT (information and communication technology); financial sector; energy supply; water transportation systems; health sector; and security services (first responders, police, military)." (Abdelgawad et al, 2018;Abdelgawad and Gonzalez, 2019) Table 2 Critical infrastructure definitions "When we consider CIs, we have to take into account that they are not simply 'physical' plants and networks. In fact, they contain not only a physical layer, but are also made of 'cyber' components and systems, and include human organisations that manage and supervise the daily operations of the infrastructure."…”
Section: Tablementioning
confidence: 99%
“…Deriving from the common points of the first two concepts found, cascading effects and CIs, the concept of critical infrastructure interdependencies, which concerns a 'mutual relationship between two or more infrastructures' (Brabcova et al, 2018), was then identified. With the increasing digitalisation and consequent linking of systems of CIs (Grafenauer et al, 2018), they are becoming more and more interconnected among each other (Franchina et al, 2008;Schauer et al, 2018), making them interdependent (Abdelgawad et al, 2018;Abdelgawad and Gonzalez, 2019;Rahnamay-Naeini and Hayat, 2016). Due to the interdependencies among CIs, the effects and the unfolding of a crisis in certain CIs become hard to predict (Hagen et al, 2015).…”
Section: Definitions and Relations Among The Identified Concepts Conc...mentioning
confidence: 99%
See 3 more Smart Citations